Portulaca bharat (Portulacaceae), a new species from Aravalli hills of Rajasthan, India - Srivastava, Amber; Chauhan, Nishant; Dash, Sudhanshu Shekhar; Singh, Sushil Kumar (Phytotaxa, 2025)
Portulaca bharat (Portulacaceae) is described and illustrated as a new species from the Aravalli hills (Jaipur, Rajasthan, India). The new species belongs to the subg. Portulaca sect. Neossia having opposite leaf, and it resembles the Linnaean P. quadrifida in having prostrate habit, articulated stem, four petals and flowers encircled by four involucral bracts, but differs in having larger growth habit, oblong-lanceolate and slightly concave leaves, pale yellow flowers becoming creamish-white towards apex, presence of glandular hairs on stamen filaments and thick roots. A detailed morphological description is provided, along with original photos.